Emerging Roles of Alternative Pre-mRNA Splicing Regulation in Neuronal Development and Function - Norris, Adam D.; Calarco, John A. (Frontiers in Neuroscience, 2012)
Alternative pre-mRNA splicing has the potential to greatly diversify the repertoire of transcripts in multicelliular organisms. Increasing evidence suggests that this expansive layer of gene regulation plays a particularly important role in the development and function of the nervous system, one of the most complex organ systems found in nature. In this review, we highlight recent studies that continue to emphasize the influence and contribution of alternative splicing regulation to various aspects of neuronal development in addition to its role in the mature nervous system.